Controllable and extra-fast synthesis of bio-applicable silver nanoparticles with Lycium Barbarum L. aqueous extract and visible light. (24th August 2019) - Chen, Man-Tang; Zhang, Wei Kevin; Liang, Wan-Li; Li, Yu-Sang; Li, Xiao-Jun; Zhu, Li-Hua; Tang, He-Bin
ABSTRACT: Silver nanoparticles (AgNPs) possess excellent antibacterial activity, while the potential biotoxicity will limit their applications in biomedical fields. It is necessary and crucial to inhibit the toxicity effect of AgNPs. In the present work, Lycium barbarum L. ( L. barbarum ) aqueous extract was adopted to controllably and extra-fast synthesize the L. barbarum modified AgNPs (L-AgNPs) under visible light. Effects of L. barbarum concentration and illumination time were investigated, and the yield of L-AgNPs reached 100% under the optimized conditions. The formation mechanism under visible light has also been put forward. A certain amount of L. barbarum aqueous extract was adsorbed on the L-AgNPs, which was confirmed by the results of FTIR and EDX. The obtained L-AgNPs exhibited excellent antimicrobial activities, in which the adsorbedaqueous extract exerted important regulating effect. Moreover, MTT-test showed that the L-AgNPs possessed good biosafety for their negligible cytotoxicity, which potentially could be used in biomedical fields. GRAPHICAL ABSTRACT: